Assessment of Drinking Water Safety in Public Primary Schools in Southern Nigeria: Implications for School WASH and SDG 6 - Aniyom, Gift; Antor, Ndep; Amadi, Ubanna O.; Samson, Chinenye C.; Rosemary, Egena (British Journal of Healthcare and Medical Research, 2026)
This study formed part of a broader assessment of Water, Sanitation and Hygiene (WASH) facilities and services in public primary schools in Akwa Ibom and Cross River States, Nigeria. This study assessed the physical, chemical and bacteriological quality of drinking water sources available in public primary schools in Akwa Ibom and Cross River States, Nigeria. A comparative cross-sectional study design was employed involving sanitary risk assessments and laboratory analysis of water samples collected from 40 public primary schools located in urban and rural communities. Water quality parameters assessed included pH, turbidity, electrical conductivity, total dissolved solids (TDS), temperature, total coliforms, and Escherichia coli (E. coli). Access to safe drinking water in schools is essential for protecting child health and achieving Sustainable Development Goal (SDG) 6. Results showed that boreholes and tube wells were the predominant sources of drinking water, accounting for 77.5% of all water facilities assessed. Despite the widespread use of improved water sources, bacteriological contamination was common. 18(45%) of the sampled schools had drinking water contaminated with E. coli, indicating faecal contamination and potential health risks to pupils. While all samples complied with World Health Organization (WHO) standards for electrical conductivity, temperature, and TDS, only a small proportion met the recommended pH standard. Significant differences were observed between schools in Akwa Ibom and Cross River States regarding access to improved water sources and levels of bacteriological contamination (p < 0.05). The findings demonstrate that access to improved water sources does not necessarily guarantee microbiologically safe drinking water. Strengthening routine water quality monitoring, implementing point-of-use treatment technologies, and integrating water safety planning into school WASH programmes are critical for reducing waterborne disease risks and accelerating progress toward SDG 6 and SDG 4a in Nigeria.